(3cJGH fhGOQ GdCKQ aj Ydj NjQ GdHTQs - (3Gdbej, CHh eMeO, , LYaQ Hf CMeO Hf Ydj, J (B381 (3g`s ((3YHO GdMejO Hf eMeO GdCUagGfjs)
(3ChdgG (B:s
(3CMeO Gddg hCSJYjfg(B... (3SFdJ CjOc Gddg Cf CLeY dc ef Qhi CYf YdjG Ydjg GdSdGe NjQ GdHTQ(B... (3hSejJg(B... (3aef Qhi Pdc LGHQ Hf YHO Gddg(B...s
(3BNQgG (B:s
(3hCfG bQjH efge aSeYJg jbhd(B: (3CeG JQVi Cf Jchf CfJ CNj aj GdOfjG hGdBNQI hCfJ NjQG efj aj GdOfjG hGdBNQI(B. (3Je GdcJGHs
(3JHUQI GdeDda (B:s
(3GdeYQha H`(B: (3GHf GdQGRjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI; HQbe(B: 1837s
(3GdPQjYI; HQbe(B: 1837s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs